Suicide Prevention Gatekeeper Training: Can They Advance Prevention in Indian Country?. Issue 3 (2nd July 2016) - Cwik, Mary F.; Tingey, Lauren; Wilkinson, Rebecca; Goklish, Novalene; Larzelere-Hinton, Francene; Barlow, Allison
Abstract : American Indian youth have the highest suicide rates in the United States; however, many do not use services and access barriers exist. This study was a cross-sectional evaluation of 6 gatekeeper trainings conducted on 1 reservation with N = 84 individuals. Analyses examined participant characteristics, impact on training objectives, and satisfaction. The majority of participants were American Indian and female (89.3%). Significant increases in knowledge (p < 0.001) and self-efficacy (p < 0.001) were observed post-test, as well as high satisfaction (3.53/5) and intent to use skills daily (36.4%) or monthly (66.3%). Lowest rated was how the training addressed cultural differences (2.93). While results support the promise of gatekeeper training, they identify a clear need for adaptation; specific implementation and research recommendations are discussed.